Structure of native alpha 2-macroglobulin and its transformation to the protease bound form. - Bretaudiere, J P (1988)
Well-preserved structures of native and alpha-chymotrypsin-bound alpha 2-macroglobulin were obtained by electron microscopy. Computer processing of these images has shown that the native structure has the shape of a padlock 19 nm long. It is proposed that the native alpha 2-macroglobulin consists of the juxtaposition of two protomers with one protomer shaped like a distorted letter "S" and with the other its reverse image, to form a binding site between the two protomers near the bottom of the complex. On cleavage of the subunits with chymotrypsin, the native structure condenses to 16.7 nm and rearranges so that the interaction between the protomers is near the middle. Two images of the alpha 2-macroglobulin-chymotrypsin conjugate were obtained. We suggest that these images represent the end and side view of this complex. Based on the manner in which the native structure is assembled, we propose that the proteolyzed form of alpha 2-macroglobulin is functionally asymmetric in that both protease binding sites reside on the same half of the complex.